The Genetic Aspect of Non-Syndromic Cleft Lip and Palate towards Candidate Genes in the Etiology : A literature Review - Mala Kurniati; RM Coen Pramono D; Agung Sosiawan; Ni Wayan Tirtaningsih (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cleft lip and cleft palate (CL/P) is a cleft lip deformity indicated by an opening or an uncommon cleft inthe lip or roof of the mouth (palate). The differences in ethnicity, gender, and the correlation with geneticfactors influence the prevalence of Non-syndromic CL/P. This study was conducted through a literaturereview on genes that were allegedly associated with Non-syndromic CL/P. Genetics play a role, to a greateror lesser extent, in all diseases. Besides, palatogenesis involves many diverse genes in a complex process.In this case, oral cleft phenotypes develop when this process is disrupted in some manner because of genedysfunction. Various genetic approaches, including genome-wide and candidate gene association studiesas well as linkage analysis, have been undertaken to identify etiologic factors, but results have often beeninconclusive or contradictory. Therefore, it concludes that the genetic basis of CL/P is still controversialbecause of the genetic complexity of clefting